Penerapan Media Alat Bantu Box untuk Meningkatkan Hasil Belajar Lompat Jauh Gaya Jongkok Siswa SD Negeri 30 Mataram - Winarni Winarni (Jurnal Paedagogy, 2021)
This study aims to improve the learning outcomes of the squat-style long jump through the application of media box tools for students of SDN 30 Mataram. This research method uses classroom action research. The subjects of this study were 15 fifth grade students at SDN 30 Mataram. The research instrument uses observation, tests, and questionnaires. The data analysis technique of this research used descriptive qualitative and quantitative analysis. The results showed that the squat style long jump learning through the use of boxed media could increase students' focus and activeness as well as a pleasant learning atmosphere, so that it was proven to improve student learning outcomes.